Synthesis of some 1 8 Naphthyridine Derivatives with Comparative Studies of Cyclization in Two Different Acids - Anwair, Massud A. S (International Journal of Pharmaceutical & Biological Archive, 2012)
Synthesis of some 1 8 Naphthyridine Derivatives with Comparative Studies of Cyclization in Two Different Acids